Analisis pendapatan dan laba sebelum dan selama pandemi Covid-19 - Apandi, Aden; Syamsuar, Ginanjar; Sumitro, Sumitro (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The impact of the Covid-19 pandemic has made many business sectors experience difficult times, both in small, medium and large industries, so this study aims to find out and analyze whether there were differences in revenue and profit before and during the COVID-19 pandemic. The method used is descriptive quantitative. The sample in this study were 50 UMKM respondents in Pulo Gadung. Testing the data using descriptive statistics with normality test, and wilcoxon marked ranking test. The results of the first study showed that there was no difference in revenue before and during the covid-19 pandemic, and the second test showed that there was a difference in profit before and during the covid-19 pandemic.